Microscopic oil displacement effect of nitrogen oil-based foam - LI Shaopeng; HU Zhiheng; YAO Zengyang; SHANG Fanhe; LI Songyan (Youqi dizhi yu caishoulu)
In low-permeability oil reservoirs， nitrogen flooding is prone to cause gas channeling， resulting in a low recovery. Nitrogen oil-based foam flooding has enhanced energy and remediation advantages to avoid damage to water-sensitive reservoirs and can effectively improve the development efficiency of such oil reservoirs. Therefore， a new type of nitrogen-oil-based foam system was constructed， and related research was carried out. Firstly， the performance of the foam system was evaluated by assessing the interfacial rheology of the foaming agent and the liquid retention rate of the foam. Subsequently， the foam occurrences in porous media were studied to understand its performance in formation. Finally， the microscopic model displacement experiments were conducted to investigate the displacement effects of three oil recovery methods： conventional nitrogen flooding， nitrogen flooding with a foaming agent dissolved in crude oil， and nitrogen oil-based foam flooding. The results show that the nitrogen oil-based foam system composed of 0.7% Span20 and 0.8% FSA-99 has good stability and a relatively high viscoelastic modulus. After 40 minutes， the liquid retention rate of the foam can still reach 50.1%. After 1.5 h at 80 °C， more than 40% of the bubbles in the porous medium were still smaller than 200 μm， indicating that the oil-based foam of the compound system has good temperature resistance. By comparing three different methods of oil recovery， it is found that when nitrogen gas comes into contact with crude oil containing foaming agents， an oil-based foam is produced. This foam can seal the gas channel after gas channeling occurs， increasing the sweep efficiency and enhancing the recovery. Compared with the first two oil recovery methods， nitrogen oil-based foam flooding has a better effect， which can inhibit the formation of channels for gas migration in the early stage of displacement and use the crude oil in the non-mainline area， with the final recovery reaching 69.95%.